Resiliensi Desa Kedonganan dalam Pembangunan Daya Tarik Wisata (DTW) Kabupaten Badung di Era New Normal - Ni Kadek Purnamasari Dewi; Putu Eka Purnamaningsih; Putu Dharmanu Yudharta (CV. Lenggogeni Data Publishing, 2023)
ABSTRACK Kedonganan Tourism Attraction is one of the pillars of the village economy, the majority of which work in the tourism sector. Kedonganan Tourist Attraction consists of Kedonganan beach, cafes along the Kedonganan beach, and Kedonganan fish market (mina wisata). This has undergone significant changes due to the impact of the Covid-19 pandemic. Kedonganan Tourism Attraction has experienced a decline in tourists, resulting in the non-operation of the tourism attraction area for two years. Community resilience is needed as an effort to deal with a change in the order of people's lives due to a disaster. This study aims to determine the resilience of Kedonganan Village in the Development of Tourist Attractions in Badung Regency in the New Normal Era. This study uses qualitative research methods with data collection in the form of observation, interviews, and documentation. Community resilience theory according to Norris et al. (2008) is used as the basis for this research analysis. The results of the study show that Kedonganan Village has succeeded in achieving a resilient community as evidenced by indicators of economic development, social capital, information and communication, and community competence which show the level of survival and adaptation of a community in Kedonganan Village. Keywords:, , ,